COMMENTS ON THE GENERAL RECOMENDATION Nº35 OF CEDAW COMMITTEE (Perspectivas de las Ciencias Económicas y Jurídicas, 2018)
This article discusses the recent General Recommendation n ° 35 (hereinafter RG 35) of the Committee of the Convention on the Elimination of All Forms of Discrimination against Women. Through the analysis of numerous documents, the aim is to show how international legislation is modified, complementing and adapting to the changing manifestations, multiple forms and modalities of violence against women. The dynamism of the phenomenon of violence against women and its persistence has made different treaty bodies also establish as a priority the fight against all forms of discrimination and violence against women and girls, some of which we analyze together with the recent recommendation, especially the reports and observations made to our country. This is due to an increasingly profound conviction of the integral, non-regressive, interdependent and indivisible character of human rights.
Keywords: General recommendation nº 35; CEDAW